Differentiating haemostasis from thrombosis for therapeutic benefit - McFadyen, James D.; Jackson, Shaun P. (Thrombosis and Haemostasis, 2013)
The central role of platelets in the formation of the primary haemostatic plug as well as in the development of arterial thrombosis is well defined. In general, the molecular events underpinning these processes are broadly similar. Whilst it has long been known that disturbances in blood flow, changes in platelet reactivity and enhanced coagulation reactions facilitate pathological thrombus formation, the precise details underlying these events remain incompletely understood. Intravital microscopy studies have highlighted the dynamic and heterogeneous nature of thrombus development and demonstrated that there are considerable spatiotemporal differences in the activation states of platelets within a forming thrombus. In this review we will consider the factors regulating the activation state of platelets in a developing thrombus and discuss how specific prothrombotic factors may influence this process, leading to excessive thrombus propagation. We will also discuss some potentially novel therapeutic approaches that may reduce excess thrombus development whilst minimising bleeding risk.
Keywords: Thrombosis; atherothrombosis; antiplatelet agents